Efektivitas EFEKTIVITAS MODEL PEMBELAJARAN CTL (CONTEXTUAL TEACHING AND LEARNING) TERHADAP KEMAMPUAN PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII SMP NEGERI 3 RAKIT KULIM - Astuti, Puji; Ningsih, Sri Yunita; Mustika, Helma; Fitri, Ramadhani; Hartati, Yunisa Fadhilah; Krisnawati, Krisnawati (LPPM Institut Pendidikan Nusantara Global, 2023)
The study aims to determine the effectiveness of the CTL (Contextual Teaching and Learning) learning model on the ability to understand mathematical concepts in class VIII students of SMP Negeri 3 Rakit Kulim. This type of research is a quasi-experimental. The research design used was the Randomized Subjects Posttest Only Control Group Design. The population in this study were all students of class VIII SMP Negeri 3 Rakit Kulim. The Sampling technique is Nonprobability Sampling. Class VIII.B was selected as the experimental class and class VIII.A as control class. The data collection technique used in this study was a test of the ability to understand mathematical concepts in the form of essay questions. Data analysis techniques in this study used the Normality Test, Homogeneity Test and Hypothesis Test. Based on the result of research on the two sample classes, it was found that form the results of data analysis with the T-test, the result of Sig. < α is 0,00 < 0,05. Then the decision taken is to accept H1 and reject H0. Thus there is a significant difference between the average student learning outcomes in the experimental class using the CTL (Contextual Teaching and Learning) model which is better than the control class. So it be concluded that CTL (Sontextual Teaching and Learning) learning is effective on the ability to understand mathematical concepts in class VIII students of SMP Negeri 3 Rakit Kulim.